Phát triển tư duy phản biện, tư duy sáng tạo cho sinh viên trong dạy học kiến thức tiếng Việt ở tiểu học bằng xây dựng ngân hàng ngữ liệu - Lê, Phương Nga; Nguyễn, Thị Hiên (Tạp chí Giáo dục, 2025)
Educational reform requires learners not only to acquire knowledge but also to develop critical and creative thinking to adapt to modern society. Yet, Vietnamese language teaching in primary schools and teacher training remains focused on description and classification, with limited attention to communication and higher-order thinking. Pre-service teachers often lack independent judgment and evaluative skills, leading to limitations in teaching quality. This study shows their critical and creative thinking is weak, largely due to passive learning habits and insufficient practice opportunities. Drawing on theoretical and practical foundations, the research designed and piloted a linguistic corpus for Vietnamese language education. Findings confirm that the corpus is an effective tool for enhancing analysis, evaluation, and creativity among students, lecturers, and teachers. It also serves as an open resource and training environment for critical and creative thinking. The study highlights the potential to expand trials and integrate digital technologies and artificial intelligence to improve applicability in teacher education and Vietnamese language instruction.